STATEGI FOOD AND AGICULTURE ORGANIZATION DALAM MENGATASI KRISIS PANGAN AKIBAT CUACA EKSTRIM DI SUB-SAHARA: FOOD AND AGICULTURE ORGANIZATION STATEGIES IN OVERCOMING THE FOOD CRISIS DUE TO EXTREME WEATHER IN SUB-SAHARA - Al Farauqi, Mohamad Dziqie Aulia; Marantika, Rofiyana Sri (Department of International Relations, Universitas Mulawarman, 2024)
Sub-Saharan Africa is one of the regions that contributes the least to global climate changes, however, it is one of the most vulnerable regions to affected by the climate change and extreme weather. In addition to climate factors, the low level of economic and technological development in Sub-Saharan Africa is also one of the factors that this country is hit by a food and human crisis. FAO (Food And Argiculture Organization) contributes to overcome the problem of food security around the world, and guarantees human freedom from hunger. This study discusses the strategy of the International Food and Argiculture Organization (FAO) in dealing with food and human security problems due to climate change and extreme weather in sub-Saharan African countries. With the help of FAO, countries in Sub-Saharan Africa can implement several programs that provide benefits, especially for food, agriculture and animal husbandry. The purpose of this study was to identify and describe FAO's strategy in dealing with the food crisis caused by extreme weather in Sub-Saharan Africa. This study uses a qualitative method. In analyzing this research, the concepts of food security and Transnational and Interstate Interactions are used to analyze the role of FAO (Food and Agriculture Organization) in providing technical assistance in agriculture for food security in Sub-Saharan Africa. FAO as an international organization is the initiator and facilitator of non-state actors who seek to overcome food and human security problems caused by extreme weather.